Escalamiento del cultivo de células en suspensión de Azadirachta indica (NEEM) en biorreactor tanque agitado para la produccion de azadiractina - Sánchez-Ordoñez, David Leonardo (Instituto Tecnológico de Costa Rica, 2014)
The following Master’s Thesis engages in the area of NeuroMuscular Electrical Stimulation (NMES), which comprises the activation of nerves and muscle fibers by applying electrical current pulses using two electrodes placed on the skin. NMES has great potential to serve as strength training, rehabilitation and post-exercise recovery tool. A conductive electrolyte (gel) is applied between the electrodes and the skin to obtain lower contact impedance and prevent skin damage; nevertheless, these systems need to improve to obtain a more uniform distribution of the electric current throughout the electrodes. Therefore, the need to study the electrical characteristics of the gel-skin interface arises. In this Master’s Thesis a 3D Finite Element Model based on experimentally obtained parameters is described and developed to simulate the electrical behavior of the gel-skin interface and obtain said characteristics. A series of simulations are performed to determine the group of signal parameters and electrode configuration that achieve the best uniformity in electrical current distribution throughout the gel-skin interface. In the end, the guidelines to obtain said uniform distribution are listed.
Proyecto de Graduación (Maestría en Electrónica) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería Electrónica, 2014.
Keywords: Interfaz; Métodos eléctricos; Métodos elementos finitos; Electrodos